Pengaruh Penggunaan Media Pembelajaran Interaktif terhadap Motivasi Belajar Siswa Sekolah Dasar (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This study uses a qualitative method to examine the effect of the use of interactive learning media on elementary school students’ learning motivation. The focus of this study is to understand how learning media that involves active interaction can increase students’ interest and enthusiasm in the learning process. Data were collected through observation, in-depth interviews with teachers and students, and documentation of learning activities. The results of the study indicate that interactive learning media can create a more interesting and enjoyable learning atmosphere, thus triggering a significant increase in student learning motivation. In addition, the use of this media also helps students understand the subject matter more easily and effectively. This study provides an overview that the integration of technology in learning can be an effective strategy to improve the quality of education in elementary schools. These findings are expected to be a reference for teachers and curriculum developers in optimizing the use of interactive learning media to improve student motivation and learning achievement.